Production and Characterization of Polymer Blend From LDPE and Starch - Muhammad Alif Afnan, Ramli (2012)
Polymer blend is an alternative polymer to substitute a common polymer used in industrial. It acts same as the others polymer. The resource to make polymer blend is from the natural polymer. The combination of natural polymer and other polymer is called polymer blend. In this study, tapioca starch and low-density polyethylene (LDPE) had been used to form the polymer blend. A compatibilizer is required in order to allow starch and LDPE to get mixed. Citric acid is one of the most readily applicable agents Function of the compatibilizer is to fragment the bond of the combination polymer due to the acidity of citric acid is propitious and the ensuing dissolution of the tapioca starch granules. The objectives of this study are to improve production of polymer blend and optimum polymer composition. Formulation that had been set are from 5, 10, 15, 20 and 25% value of starch based on LDPE. The samples first undergo extrusion process that make the samples form into pellet size. Then, the pellet had been gone through molding process which is injection molding. The pellet been shaped into dumbbell shape for testing purpose. Characteristic that had been done are like tensile strength, density and water absorption. The result expected is to show the certain formulation gives high response in the area of testing and the optimum polymer blend composition is determined.